F12 Test-retest reliability of objective measures of posture, gait and clinical scales in huntington's disease. (16th November 2010) - Bohlen, S; Ekwall, C; Wiklund, L; Rumpf, S; Reilmann, R
Abstract : Background: To determine effects of interventions such as physical therapy, outcome measures of high test-retest reliability are essential. Different clinical rating scales and quantitative motor measures have been used to assess postural stability, balance and gait in different patient groups and healthy voluntiers. Little is known about the applicability of most of these measures in Huntington's disease. Aims: To investigate changes in performance of four different clinical rating scales (timed up-and-go test (TUG); Berg balance scale (BBS); one leg stance test (OLST); figure of eight test (Fig8)) and two quantitative motor techniques (velocity of gait using the GAITRite; velocity of center of mass movement on a force plate). Methods/techniques: 11 HD patients in early to middle stages of disease were tested using the above mentioned tests and were tested again after six weeks. Patients received neither physical therapy nor occupational therapy during at least three months before the first test and medication remaind unchanged. Statistical analysis was performed using non-parametric statistics (Man-Whitney-U Tests and Spearman correlations). Results/outcome: All tests showed relatively high test-retest reliability with strongest correlation for the BBS (r=0.923) and the TUG (r=0.845) for the clinical measures and for both the GAITRite (r=0.836) and the force plate (r=0.918). Furthermore, TUG and gait velocity were correlated to each other at both assessment timepoints (r=0.636, r=0.809 respectively). Comparisons between the timepoints showed no significant changes for any of the measures (p>0.1 in all cases). Conclusions: Two of the clinical tests and both technical analyses fulfil the criteria of high test-retest reliabilty. Most patients performde very well on the BBS (>50/56 points) so the high test-retest correlation might be due to a ceiling effect. We conclude that quantitative motor measures and the TUG are useful tests for interventions in HD.